Pengaruh Terapi Tambahan Asam Folat Dan Kobalamin Terhadap Gejala Skizofrenia Kronik - Betty Hidayati; Aris Sudiyanto; Moh. Fanani (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Folic Acid, Cobalamin, Symptoms, Schizophrenia. Schizophrenic patients have low levels of folic acid and cobalamin. Deficiency of folic acid and cobalamin can cause neurological and psychiatric disorders. Supplementation of folic acid and cobalamin may provide therapeutic benefits through different mechanisms of current treatment regimens. To assess the effectiveness of additional therapies of folic acid and cobalamin in improving the negative symptoms and length of stay of chronic schizophrenic patients. This study was an experimental study with randomized controlled trial group, pre-post test design. The intervention group had significant PANSS score improvementin positive symptoms (p = 0,01), negative symptoms (p = 0,004), general psychopathologies (p = 0,01) and PANSS total score (p = 0,014) subscales. ONE-WAY ANAVA statistic analysis result shows significant reduction in all four subscales (p = 0,000). Adding folic acid and vitamin B12 as adjuvant therapy with standard antipsychotic medication effective in reducing chronic schizophrenia symptoms.